2016
DOI: 10.3109/01658107.2016.1173709
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Coherence Tomographic Profile of Leber Hereditary Optic Neuropathy

Abstract: The objective of this study was to describe the changes in the retinal ganglion cell complex (GCC) relative to the retinal nerve fibre layer (RNFL) over time in Leber hereditary optic neuropathy (LHON) patients. Average RNFL and GCC thickness was measured in seven patients in the early acute (123, 68.4 μm), late acute (113.5, 57.4 μm), and chronic (72.7, 50.8 μm) phases. Patients showed thinning of the GCC with RNFL swelling in the early acute phase. GCC thinning became severe within weeks and persisted. RNFL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
1
10
0
3
Order By: Relevance
“…Some studies have reported that pRNFL thickness initially increases and then decreases along with the course of LHON, with significant thinning of the pRNFL in the chronic stage. [3][4][5] However, only a few studies have focused on subsequent pRNFL thickness changes in patients with chronic LHON having different disease courses.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that pRNFL thickness initially increases and then decreases along with the course of LHON, with significant thinning of the pRNFL in the chronic stage. [3][4][5] However, only a few studies have focused on subsequent pRNFL thickness changes in patients with chronic LHON having different disease courses.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that thickening of RNFL or GCC may be a precursor of acute vision loss in LHON, as previously suggested. 8,13 VEP signals were normal in the presymptomatic period; P100 amplitudes decreased only after vision loss. One year after symptom onset, pERG showed mildly decreased amplitude of the N95 component, suggesting loss of ganglion cell function.…”
Section: Discussionmentioning
confidence: 87%
“…1). 3,8 VEP P100 signal amplitudes (RETI-Port/scan, Roland Consult, Brandenburg, Germany) were mildly decreased in the right (affected) eye and normal in the left (unaffected) eye (4 mV OD, 7 mV OS at 60 minutes) at presentation. P100 latency was unaffected (80 ms OD, 106 ms OS at 60 minutes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(19)(20)(21) OCT is used to monitor for progressive visual deterioration in several diseases and has been shown to detect changes in RNFL thickness before functional vision loss. (22)(23)(24) Therefore, in FD, RNFL thickness may serve as a biomarker to identify patients at risk of developing ON, as well as those with early stage disease. (25,26) The purpose of this study was to determine the utility of OCT in characterizing the presence and manifestations of ON in FD.…”
Section: Introductionmentioning
confidence: 99%